Retirement decision and household's gasoline consumption: Evidence from a Regression Discontinuity Design - Nicola Francescutto (University of Neuchâtel, Institute of Economic Research (IRENE), 2024)
I employ household-level data over 2006-2017 to quantify the impact of retirement on gasoline consumption. Based on a fuzzy regression discontinuity design, I show that gasoline consumption declines by 32-36 percent on average over my different specifications. The reduction reaches 59-66 percent when I restrict the sample to single-person households. I further find that the probability to use any gasoline decreases by 5-6 percent at retirement (13-16 percent for single-person households). These findings suggest that demographic trends represent an important driver of CO2 emissions associated with private mobility in developed countries.
Keywords: C21; C23; D12; Q4; 330; gasoline consumption; retirement effect; Household expenditure survey; fuzzy regression discontinuity design